PENDAMPINGAN GURU DALAM MEMBANTU KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS 1 SEKOLAH DASAR - Putri Ayuningsih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Early reading skills develop through learning experiences that are strongly shaped by the quality of interaction between teachers and students, particularly when children experience difficulties reading independently. This study aimed to describe how teacher assistance supports the development of early reading skills among a first-grade student at SD Islam Al-Ukhuwah Cikarang. A qualitative descriptive approach was employed, involving one classroom teacher and one student selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings revealed that the student tended to avoid reading activities when direct assistance was unavailable. In contrast, the integration of guided reading, purposeful verbal communication, and gradual support based on scaffolding principles encouraged the student to engage with the text, maintain attention, and demonstrate increasing confidence while reading. These findings suggest that the effectiveness of teacher assistance depends more on the teacher's ability to adapt instructional support to students' learning responses than on the implementation of a single instructional strategy. This study contributes to the understanding of verbal communication as a pedagogical mechanism that integrates guided reading, scaffolding, and individualized instruction to facilitate the development of early reading skills among elementary school students experiencing reading difficulties. ABSTRAK Kemampuan membaca permulaan berkembang melalui proses belajar yang dipengaruhi oleh kualitas interaksi antara guru dan siswa, terutama ketika peserta didik masih mengalami hambatan membaca secara mandiri. Fenomena tersebut mendorong penelitian ini untuk mendeskripsikan bentuk pendampingan guru dalam membantu kemampuan membaca permulaan pada siswa kelas I SD Islam Al-Ukhuwah Cikarang. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif yang melibatkan satu guru kelas dan satu siswa sebagai informan yang dipilih secara purposive. Data dihimpun melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model analisis interaktif melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian memperlihatkan bahwa siswa cenderung menghindari aktivitas membaca ketika tidak memperoleh pendampingan secara langsung, sedangkan penerapan guided reading, komunikasi verbal yang terarah, serta pemberian bantuan bertahap berdasarkan prinsip scaffolding mendorong siswa mulai mengikuti bacaan, mempertahankan perhatian, dan menunjukkan keberanian membaca secara bertahap. Temuan ini menegaskan bahwa efektivitas pendampingan lebih ditentukan oleh kemampuan guru menyesuaikan bentuk bantuan sesuai respons belajar siswa daripada oleh penggunaan satu strategi pembelajaran tertentu. Kontribusi penelitian terletak pada penjelasan bahwa komunikasi verbal menjadi mekanisme pedagogis yang mengintegrasikan guided reading, scaffolding, dan pembelajaran individual dalam mendukung perkembangan kemampuan membaca permulaan pada siswa sekolah dasar yang mengalami hambatan membaca.